2023
DOI: 10.1080/22221751.2023.2270071
|View full text |Cite
|
Sign up to set email alerts
|

Previous exposure to Spike-providing parental strains confers neutralizing immunity to XBB lineage and other SARS-CoV-2 recombinants in the context of vaccination

Rahul K. Suryawanshi,
Taha Y. Taha,
Maria McCavitt-Malvido
et al.

Abstract: The emergence of SARS-CoV-2 recombinants is of particular concern as they can result in a sudden increase in immune evasion due to antigenic shift. Recent recombinants XBB and XBB.1.5 have higher transmissibility than previous recombinants such as “Deltacron.” We hypothesized that immunity to a SARS-CoV-2 recombinant depends on prior exposure to its parental strains. To test this hypothesis, we examined whether Delta or Omicron (BA.1 or BA.2) immunity conferred through infection, vaccination, or breakthrough i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…However, we found that four-weeks post-dose four the BA.1 and BA.5 bivalent vaccines boosted the ability of WH1 RBD-specific Bmem to bind antigenically distinct subvariants including those not contained in the bivalent vaccines, BQ.1.1 and XBB.1.5. This expands on previous analyses of NAb, which showed improved recognition of XBB and other related subvariants following the BA.5 bivalent mRNA vaccine or an Omicron BTI (14,15,39,49). Therefore, we reveal novel evidence that cross-reactive Bmem binding both WH1 and Omicron subvariants are boosted by a bivalent fourth dose.…”
Section: Discussionsupporting
confidence: 83%
“…However, we found that four-weeks post-dose four the BA.1 and BA.5 bivalent vaccines boosted the ability of WH1 RBD-specific Bmem to bind antigenically distinct subvariants including those not contained in the bivalent vaccines, BQ.1.1 and XBB.1.5. This expands on previous analyses of NAb, which showed improved recognition of XBB and other related subvariants following the BA.5 bivalent mRNA vaccine or an Omicron BTI (14,15,39,49). Therefore, we reveal novel evidence that cross-reactive Bmem binding both WH1 and Omicron subvariants are boosted by a bivalent fourth dose.…”
Section: Discussionsupporting
confidence: 83%
“…Rep-WT, Rep-ORF8-stop, icXBB.1.5, and icXBB.1.5+ORF8 were generated following pGLUE method in the pBAC SARS-CoV-2 construct as previously described (22). Briefly, the SARS-CoV-2 genome was divided into 10 fragments, which were cloned and later ligated via BsaI digestion and Golden Gate assembly protocol as described by Taha et al (22,37). The ligated plasmid was confirmed via nanopore sequencing (Primordium Labs).…”
Section: Infectious Clone and Replicon Generationmentioning
confidence: 99%